Narrative of a second voyage in search of a north-west passage [electronic resource] : and of a residence in the Arctic regions during the years 1829, 1830, 1831, 1832, 1833 - Ross, John, Sir, 1777-1856; Ross, James Clark, Sir, 1800-1862. (London : A.W. Webster, 1835)
Vol. I. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 40358-40360. Errata--Following Advertisement. Electronic reproduction. Mode of access: Internet. 44